A multi-centre study using comprehensive geriatric assessment to determine differences between older women with operable breast cancer undergoing surgery or non-operative treatment - Parks, R; Howard, P; Zahit, Ross Azura; Kayani, A; Lakshmanan, R; Tang, S; Cheung, K (Springer Verlag, 2020)
Aims/Objectives: Shared decision making on the choice of treatment for older women with breast cancer involves many factors. Comprehensive geriatric assessment (CGA) is recognised to have a role in older patients with cancer, but how this should be utilised is still debatable. A pilot study involving older women newly diagnosed with early operable primary breast cancer was conducted aiming to explore the potential value of CGA. Methods: Decision of primary treatment followed consultation with the clinical team and was not guided by any aspect of this study. CGA, using a validated cancer-specific tool from our collaborator, A Hurria, was conducted within 6 weeks after diagnosis, regardless of date of surgery/first treatment. A total of 178 female patients aged ≥70 years with a new diagnosis of early (stage 1 or 2; cT0-2, N0-1, M0) operable primary breast cancer proven histologically, were thus far recruited from three UK centres. Results: Among these 178 patients, 149 underwent primary surgery and 29 received non-surgical treatment (primary endocrine therapy (N=28) or radiotherapy (N=1)). CGA determined that increasing age (p=0.006), reduced independence with activities of daily living (ADLs) (p=0.001) and independent activities of daily living (IADLS) (p=0.001), increased number and severity of comorbidity (p=0.043), reduced Karnofsky performance status when rated both by the patient (p=0.001) and physician (p=0.003), were significantly related to non-surgical treatment within 6 weeks after diagnosis. Other CGA parameters measured which were not significant include number of daily medications, level of social support, level of social activity, cognition, number of falls, 'Timed up and go' score. Conclusions: The pilot study has confirmed that CGA may have value in assessing this cohort of patients. Generally, it appears that patients receiving non-surgical treatment are more frail than their counterparts undergoing surgery. The study is ongoing and has expanded to include an international centre.